Applied linguistics and primary school teaching - Ellis, Sue; McCartney, Elspeth (Cambridge University Press, 2011)
"Modern primary teachers must adapt literacy programmes and ensure efficient learning for all. They must also support children with language and literacy difficulties, children learning English as an additional language and possibly teach a modern foreign language. To do this effectively, they need to understand the applied linguistics research that underpins so many different areas of the language and literacy curriculum. This book illustrates the impact of applied linguistics on curriculum frameworks and pedagogy. It captures the range of applied linguistics knowledge that teachers need, and illustrates how this is framed and is used by policy makers, researchers, teacher educators and the other professions who work with teachers in schools. It considers how to effect professional development that works. It is essential reading for primary teachers but also for speech and language therapists, educational psychologists, learning support teachers and all those doing language or literacy research in the primary classroom"--